Application and properties of selected flavanones - Błazińska, Paulina; Sykuła, Anna (Wydawnictwo Politechniki Łódzkiej, 2018)
Flavanones, secondary plant metabolites, are one of the main group of flavanoids. They are widely spread in nature in many plants. The large diversity of structural structure of flavanones and controlled methods of modifying their molecules have a huge impact on biological activity. The present review will summarize the current knowledge about occurrence, obtaining by chemical synthesis, application and bioactivity of flavanones. Also, they are received from specific chemical synthesis. Flavanones have a great biological activity. Derivatives of flavanone have many different properties such as anti-inflammatory, anticancer, antioxidant, antimicrobial or hepatoprotective activities. These natural polyphenolic compounds are used in cosmetology, pharmacy and medicine. The demand and usage on them increases.
Keywords: flavanones; flavonoids; secondary plant metabolites; biological activity; flawanony; flawonoidy; wtórne metabolity roślinne; aktywność biologiczna